2018
DOI: 10.5194/acp-2018-1020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ice nucleation activity of silicates and aluminosilicates in pure water and aqueous solutions. Part 2 – Quartz and amorphous silica

Abstract: <p><strong>Abstract.</strong> Divergent ice nucleation (IN) efficiencies of quartz, an important component of atmospheric mineral dust, have been reported in previous studies. We show here that quartz particles obtain their IN activity from milling and that quartz aged in water loses most of its IN efficiency relative to freshly milled quartz. Also, the quartz surface – much in contrast to that of feldspars – is not prone to ammonia-induced … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 115 publications
(209 reference statements)
2
8
0
Order By: Relevance
“…A lattice match exists between hexagonal ice and β-tridymite and cubic ice and β-cristobalite, but these polymorphs are not stable at low temperatures, and we do not expect them to be present in our samples . The freezing ability of another silica polymorph, quartz, has been examined previously and has been observed to be highly variable, with the warmest IN activity attributed to surface roughening and milling. , However, we suspect that the silica polymorphs in the Santiaguito and SHV ashes do not contribute significantly to the IN behavior observed in this work. Unmilled quartz has been observed to be a weaker ice nucleant than plagioclase feldspars, ,, and our ash samples were not milled or ground.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…A lattice match exists between hexagonal ice and β-tridymite and cubic ice and β-cristobalite, but these polymorphs are not stable at low temperatures, and we do not expect them to be present in our samples . The freezing ability of another silica polymorph, quartz, has been examined previously and has been observed to be highly variable, with the warmest IN activity attributed to surface roughening and milling. , However, we suspect that the silica polymorphs in the Santiaguito and SHV ashes do not contribute significantly to the IN behavior observed in this work. Unmilled quartz has been observed to be a weaker ice nucleant than plagioclase feldspars, ,, and our ash samples were not milled or ground.…”
Section: Resultsmentioning
confidence: 53%
“…The freezing ability of another silica polymorph, quartz, has been examined previously and has been observed to be highly variable, with the warmest IN activity attributed to surface roughening and milling. , However, we suspect that the silica polymorphs in the Santiaguito and SHV ashes do not contribute significantly to the IN behavior observed in this work. Unmilled quartz has been observed to be a weaker ice nucleant than plagioclase feldspars, ,, and our ash samples were not milled or ground. Additionally, the similar freezing behavior and bulk composition of all three ashes suggest that these small differences in composition do not play a role in determining the IN behavior of the Santiaguito and SHV ashes.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…to increase the INA of quartz (Zolles et al, 2015;Kumar et al, 2018b;Harrison et al, 2019). They may also, however, be the most unstable sites as (Harrison et al, 2019) observed measurable 'ageing' in quartz samples (including Atkinson Quartz and Fluka Quartz) that were immersed in room temperature water for only 1 h. Our wet heat treatment of Atkinson Quartz resulted in an INA deactivation of similar magnitude (∆T50 wet around 7 °C) to that achieved after 16 months of aqueous room temperature ageing by Harrison et al (2019).…”
Section: Silicassupporting
confidence: 49%
“…Even though desert soils contain typically < 1 % organic matter due to the low average annual precipitation (Troeh and Thompson, 2005), long-range transport of dust has been suggested to efficiently disperse bacteria on a global scale (Hara and Zhang, 2012). Enriched fluorescent particle concentrations, an indication for enriched biological material, were found in long-range transported Saharan dust by Kupiszewski et al (2015) in ice crystal residuals from mixedphase clouds in the Swiss Alps and in condensation-mode INPs at 241 K by Boose et al (2016b) on the Canary Islands. In contrast to biological material, secondary organic aerosol coatings have been observed to decrease the ice nucleation ability of dust particles in the laboratory in deposition mode (Möhler et al, 2008) but not in condensation mode (Koehler et al, 2010;Kanji et al, 2018).…”
Section: Introductionmentioning
confidence: 99%